Pengaruh Fintech Terhadap Perkembangan UMKM di Ke’te Kesu Kabupaten Toraja Utara - Devi Yanti Rante Rapa; Rati Pundissing; Mince Batara (Universitas Katolik Widya Karya Malang, 2023)
This study aims to determine the influence of fintech on the development of UMKM in Ke'Te Ke'Su, North Toraja Regency. The research method used in this study is a quantitative research method, with the population of all UMKM located in Ke'te Ke'su, North Toraja Regency. The sample in this study amounted to 40 respondents with purposive sampling techniques.The data were analyzed using the SPSS 25 measurement tool. The results of this study show that fintech has a positive and significant effect on the development of Ke'te Kesu UMKM, North Toraja Regency. The value of the coefficient of determination in this study was 0.375 or 37.5%.